Resistencia de Rottboellia cochinchinensis (Lour.) W.D. Clayton al herbicida nicosulfuron en cultivos de maiz - Delgado, M.=700 1 Ortiz Dominguez, A.; Zambrano, C.
(Es, En)
Ilus., 11 ref.
Keywords: ZEA MAYS; ROTTBOELLIA COCHINCHINENSIS; MALEZAS; ESCARDA; HERBICIDAS; RESISTENCIA A LOS PLAGUICIDAS; BIOTIPOS; VENEZUELA